Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.jval.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Nucleoside Reverse Transcriptase Inhibitor Pairs in Efavirenz-Based Regimens for Treatment-Naïve Adults with HIV Infection in the United States

Abstract: Tenofovir/emtricitabine was predicted to be more effective and cost-saving compared with abacavir/lamivudine and zidovudine/lamivudine in treatment-naïve adults with HIV-1 infection in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…External validation was undertaken using previously published costeffectiveness studies that utilized similar models. 24,[39][40][41][42] For each validation exercise, model inputs corresponding to published profiles were run within the DTG/3TC costeffectiveness model. Where model inputs were not reported, default model inputs were used, or reasonable assumptions were made.…”
Section: Model Validationmentioning
confidence: 99%
“…External validation was undertaken using previously published costeffectiveness studies that utilized similar models. 24,[39][40][41][42] For each validation exercise, model inputs corresponding to published profiles were run within the DTG/3TC costeffectiveness model. Where model inputs were not reported, default model inputs were used, or reasonable assumptions were made.…”
Section: Model Validationmentioning
confidence: 99%
“…Given that ART regimens have improved in efficacy while cost-effectiveness has held fairly stable over time (Freedberg et al, 2001), and given that patients are now recommended to begin therapy much earlier, we consider both our base case and our sensitivity analysis to be conservative. In fact, a more recent study shows that a commonly used current ART regimen (tenofovir, emtricitabine, and efavirenz; Brogan, Talbird, & Cohen, 2011) provides quality-adjusted survival gains beyond those from the ART regimen featured in our base case analysis (zidovudine, amivudine, and efavirenz), which suggests that our results underestimate the value of ART and, therefore, the societal losses from policies restricting its access.…”
Section: Discussionmentioning
confidence: 59%
“…As ART has improved and access has spread over time, life expectancy among adults living with HIV/AIDS has essentially normalized among those on therapy (Detels et al, 1998;Romley et al, 2014). ART has been shown to prolong survival (El-Sadr et al, 2006;Kitahata et al, 2009) while improving quality of life (El-Sadr et al, 2006), lowering the risk of HIV transmission (Cohen et al, 2011;Kuhn et al, 2010), reducing the risk of work-limiting disability, and increasing the likelihood of employment (Bernell & Shinogle, 2005;Goldman & Bao, 2004). Yet ART works best when taken without interruption, implying a need to minimize disruptions in access to treatments and care as a result of changes in the policy environment (El-Sadr et al, 2006;Julg & Goebel, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Observed reductions in mortality rates may be mostly attributable to improved health, so older CD4‐based mortality rates in our model may not be greatly overestimated. Although the mortality and utility values used in our model have been used consistently in other models of HIV infection , newer studies with updated results would improve confidence in our model's results.…”
Section: Discussionmentioning
confidence: 99%
“…The two US studies utilized lifetime models and analysed first‐line use of TDF/FTC and ABC/3TC in combination with EFV. The first study tracked individuals through four therapy lines, used data from an informal indirect comparison of the two NRTI backbones, and found that TDF/FTC + EFV had lower costs (3.8% lower) and slightly higher QALYs (0.4% higher) than ABC/3TC + EFV . The base‐case analysis of the second study included universal HLA‐B*5701 testing for individuals initiating treatment with ABC/3TC, assumed that TDF/FTC + EFV and ABC/3TC + EFV had equivalent efficacy, and showed that ABC/3TC + EFV resulted in lower costs.…”
Section: Discussionmentioning
confidence: 99%